Development of Android/iPhone application for image processing and searching - Zhang, Jiawei (2016)
This project is mainly about designing an Android application related to image searching and recognition. With the WeChat API, the application realize the function of comparing the captured photo with the data library for the result of target MD5 code and use the code as an index obtain the specific name of the logo in the taken photo. There are two way to approach to the detected picture, one is taking from the camera right now; another is obtain from the album in the smartphone. Also the application gives a link at the result page so that users can easily get the access to the detailed information about the logo they are looking for. Besides, this project put forward an algorithm to decrease the glares in the images that need to be recognized.